Perceived workload and organizational citizenship behavior (OCB): The role of psychological empowerment - Wijaya, Fef Rama Jaya; Purba, Debora Eflina (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
Organizational Citizenship Behavior (OCB) refers to employee behavior that is voluntary and does not attract formal rewards from organizations, but which can increase their effectiveness and efficiency. This study aims to examine the mediating effect of psychological empowerment on the relationship between perceived workload and OCB. Data were collected using the snowball sampling method and an online survey of 201 employees aged 19-50 working in various private organizations in Indonesia, particularly in the Jakarta, Indonesia (female: 54.7%; male: 45.7%). The measuring instruments used were the workload subscale of the Job Demand-Resource scale, the Psychological Empowerment Questionnaire (PEQ), and the OCB subscale of the Task Performance Scale. Data were analyzed by the mediation technique using Hayes's Macro. The results show that perceived workload positively predicted psychological empowerment (B = 0.192, p < .01) and that psychological empowerment positively predicted OCB (B = 0.2189, p < .01). The results also show that psychological empowerment mediated the relationship between perceived workload and OCB (B= 0.021, SE = 0.0160, 95% CI [0.0143, 0.0759]). From the findings, it is expected that organizations will be able to manage the workload of their employees and create positive emotions in it.